Chaos in magnetospheric radio emissions - A. C.-L. Chian; A. C.-L. Chian; E. L. Rempel; E. L. Rempel; F. A. Borotto; F. A. Borotto; F. A. Borotto (Nonlinear Processes in Geophysics, 2002)
A three-wave model of auroral radio emissions near the electron plasma frequency was proposed by Chian et al. (1994) involving resonant interactions of Langmuir, whistler and Alfvén waves. Chaos can occur in the nonlinear evolution of this three-wave process in the magnetosphere. In particular, two types of intermittency, due to either local or global bifurcations, can be observed. We analyze the type-I Pomeau-Manneville intermittency, arising from a saddle-node bifurcation, and the crisis-induced intermittency, arising from an interior crisis associated with a global bifurcation. Examples of time series, power spectrum, phase-space trajectory for both types of intermittency are presented through computer simulations. The degree of chaoticity of this three-wave process is characterized by calculating the maximum Lyapunov exponent. We suggest that the intermit-tent phenomena discussed in this paper may be observed in the temporal signal of magnetospheric radio emissions.